2020
DOI: 10.2147/cmar.s283877
|View full text |Cite
|
Sign up to set email alerts
|

<p>Regulatory Roles of Tumor Necrosis Factor-α-Induced Protein 8 Like-Protein 2 in Inflammation, Immunity and Cancers: A Review</p>

Abstract: Tumor necrosis factor-alpha (TNF-α)-induced protein 8 (TNFAIP8/TIPE) family, including TNFAIP8 (TIPE), TNFAIP8 like-protein 1 (TNFAIP8L1/TIPE1), TNFAIP8 like-protein 2 (TNFAIP8L2/TIPE2), and TNFAIP8 like-protein 3 (TNFAIP8L3/TIPE3), plays a vital role in regulating inflammatory responses, immune homeostasis, and cancer development. Over the last decade, studies have shown that TIPE2 protein is differentially expressed in diverse cells and tissues. The dysregulation of TIPE2 protein can lead to dysregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…These four members are similar in structure but appear to play diverse roles in the progression of cancer and inflammatory responses (1). TNFAIP8, also known as SCC-S2, was the first member of the TIPE family to be discovered; it not only promotes tumour cell proliferation, survival and autophagy, and induces drug resistance, but also promotes tumour invasion, migration and angiogenesis, which are closely related to oncogenesis and tumour progression (3). Meanwhile, TNFAIP8 participates in the regulation of various other diseases; for example, it inhibits the inflammation response after injury and regulates cell apoptosis in inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These four members are similar in structure but appear to play diverse roles in the progression of cancer and inflammatory responses (1). TNFAIP8, also known as SCC-S2, was the first member of the TIPE family to be discovered; it not only promotes tumour cell proliferation, survival and autophagy, and induces drug resistance, but also promotes tumour invasion, migration and angiogenesis, which are closely related to oncogenesis and tumour progression (3). Meanwhile, TNFAIP8 participates in the regulation of various other diseases; for example, it inhibits the inflammation response after injury and regulates cell apoptosis in inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Following the discovery of TIPE2 due to its elevated expression in the spinal cord tissue of mice with experimental autoimmune encephalomyelitis (EAE) ( 31 ), a growing body of evidence supports that the expression abnormality of TIPE2 plays a certain role in the pathogenesis of various inflammatory and allergic diseases and autoimmune disorders ( 32 34 ). It has been demonstrated that the TIPE2 level is reduced in the PBMCs of patients with systemic lupus erythematosus (SLE), and collagen-induced arthritis (CIA) mice with a negative correlation with the development of arthritis ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α suppression reduces the expression of all EMT markers (Snail, LOX, N-cad, and Vimentin), as in FAT1 knockdown. At the same time, nestin, which is involved in GBM cell invasion, and SOX2, a marker of stem-like cells, are not reduced by HIF-1α knockdown but are downregulated by FAT1 knockdown [ 141 , 142 ]. SOX2 expression is primarily under the control of HIF-2α [ 143 ].…”
Section: Hypoxiamentioning
confidence: 99%
“…TIPE2 (tumor necrosis factor-α (TNF-α)-induced protein 8-like 2), a member of the TNF-α-induced protein 8 (TNFAIP8, TIPE) family, maintains immune homeostasis [ 142 , 144 ] and it was demonstrated to inhibit the proliferation and invasion of different tumor cells [ 145 , 146 ]. Overexpression of TIPE2 prevents hypoxia-induced expression of β-catenin, cyclin D1, and c-myc in human glioma cells, suggesting that TIPE2 overexpression inhibits hypoxia-induced activation of the Wnt/β-catenin pathway and EMT in glioma cells [ 147 ].…”
Section: Hypoxiamentioning
confidence: 99%